تعليم اللغة العربية لأغراض خاصة لقسم "رجال الأعمال" بمعهد تزكية الإسلامي العالمي مالانج - Sugian, Arif; Joni Guci, Aslim Abdullah (Ta'limi | Journal of Arabic Education and Arabic Studies, 2024)
In essence, IIBS Tazkia Malang has international vision and prepare students of Tazkia in facing the challenges of modern developments, currently well in the field of science and behavior. Therefore, Arabic language has a strategic place in this cottage because of its nature as a scientific and international language. With this research, Researcher intend to achieve the objectives of study as follows: 1) Provide a teaching book based on concept of Arabic specific purpose for entrepreneur students in Tazkia International Islamic Boarding School, Malang. 2) Knowing the effectiveness of a teaching book based on concept of Arabic specific purpose for entrepreneur students in Tazkia International Islamic Boarding School, Malang. This research uses research and development (R&D) method with qualitative and quantitative approach. Researcher also used the ADDIE's development research steps that are: analysis, design, development, implementation and evaluation. The techniques to collect date are observation, interview, questionnaire and test. And data analysis using descriptive analysis and descriptive statistical analysis. The result of this research is a teaching book consisting of four units, that are: entrepreneur for culinary, entrepreneur for services, entrepreneur for agribusiness and entrepreneur for preserving the environment. And teaching books that have been prepared are effective to improve student's ability in Arabic language. This result is seen when the researcher compared the pre test and post test result obtained by the students, and the value of t (count) in this research (3, 88) is bigger than the value of t (table) (1, 77) at 5 0/n degree and (2, 65) at 1% degree.